Tramas comunicacionais e procedimentos de criação: por uma gramática do livro de artista - Neves, Galciani (2009)
This dissertation approaches the communicational, plastic, and symbolic aspects of the processes of constructing an artist s book, which is a hybrid artistic manifestation, an object hard to conceptualize, and therefore in need of critical attention in contemporary debate. The Process Critique articulated by Cecilia Salles, based on Charles Sanders Peirce s semiotics, acts as theoretical device in guiding the organization of possible artistic references to the object of study, the creation of a brief survey of the production of artist s book in Brazil, the process of interview-dialogue with artists, and the elaboration of the eleven fields of operation in the creation of the artist s book. The object of study is discussed as signifying process (semiosis), i.e., as a continuous, unfinished, non-linear, inferential process, one that is open to chance e to the introduction of new ideas to be tested and transformed (or not) in possibilities of works of art and whose trajectory is maked by communicative questions throughout. The methodology consists of theoretical revision and interviews with artists about the creation of their work, which served as a major source of information in the deeper understanding of the various deployments in the creation of an artist s book. The contexts in the creation of the works are also discussed, including the inter-relations between certain works, the media, the references, the transformations of the raw material, the creative tendencies, the artist s perception of space, time, and memory, the forms of appropriation, and the use of language. The research aims at establishing possibilities to reposition rigid conceptualizations of the artist s book, and open new ways in which to understand its complex networks of creation, where multiple forms of language flow and interact